Pengaruh Devisa, Kurs Dollar AS, PDB dan Inflasi Terhadap Impor Mesin Kompressor dari China - Wira Satrya Wiguna, Ida Bagus; Suresmiati D., A.A. Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 5, Mei 2014 (pp.173- 226), 2014)
Import is the government policy in the field of international trade served to increase national economic growth. This study aimed to determine whether there is a significant effect of foreign exchange, U.S. dollar exchange rate, GDP and inflation on imports of Chinese machinery compressor period 1996-2012. Objects in this research is the engine compressor imported from China. The analysis used is multiple linear regression, simultaneously testing and partial testing. Results if the data show simultaneous exchange, the U.S. dollar exchange rate, GDP and inflation have a significant effect on the import of machinery compressor from China period 1996-2012, with a coefficient of determination ( R 2 ) of 0.885 means that 88.5 % variation in engine compressor imported from China influenced the period 1996-2012 by variations in foreign exchange, the U.S. dollar exchange rate, GDP and inflation, with the remaining 11.5 % is influenced by a number of other variables that are not included in this study. Foreign exchange and inflation does not affect the partial positive and significant, but positive and significant effect of GDP, while the U.S. dollar exchange rate is partially negative and significant effect on the import of machinery compressor from China period 1996-2012.
Keywords: Import; Foreign Exchange; Foreign Exchange; Gross Domestic Product (GDP); inflation